Geoscience education using virtual worlds: the Unicam Earth Island project - Boniello, Annalisa (RESEARCH TRENDS IN HUMANITIES Education & Philosophy, 2017)
This research was aimed at a new approach in geoscience education using a Multi User Virtual environment (Muve), defined Virtual World. The experience takes place in a 3D virtual island, called Unicam Earth, built for this research project on a server of the University of Camerino The Unicam Earth Island is a virtual platform where students and teachers can study, collaborate and create scientific activities on geosciences This study reports the results of the experimentation carried out on a group of classes of Middle and High schools in Italy, in the area near Napoli, comprising 520 students and 83 teachers. The science teachers have been involved as well, to investigate how and to which extent an innovative strategy could improve the teaching of geoscience in Italian school.